Text neck: a modern concern - Badkur, Seema; S., Keerthana; Kamble, Mugdha; Shrivastava, Shweta; Jain, Nidhi (International Journal Of Community Medicine And Public Health, 2023)
Background: Nowadays, the mobile phone is the most popular and widely used device for various daily activities. Text neck used to describe neck discomfort and injury of upper back muscle which is caused by the frequent forward bending of neck at various angles, while staring down at a mobile phone. This should consider as “pain of the modern era” since it is caused by modern-era gadgets. The text neck syndrome is a growing health concern and has the potential to affect millions of people all over the world. The objectives of the study were to assess the burden of text neck syndrome and to find out the effect of neck disability on daily activities. Methods: A cross sectional study was conducted among adults aged between 18-50 years from the general population using neck disability index questionnaire to gather information on how neck pain affected one’s ability to function in everyday life. Results: Out of 691 responses, 95.8% were the mobile phone uses and 36.2% were on mobile phone for 5-7 hours per day. 27.4% were experiencing the mild neck pain. 45.6% of respondents reported mild text neck disability, 14.5% reported moderate, 3% reported severe and 0.4% reported complete text neck disability, and 36.5% did not suffer text neck disability. Conclusions: A person’s life is incomplete without mobile phones, so that timely interpretation and interventions along with good knowledge about postural correction will be the key entities to deal with text neck syndrome.